2015
DOI: 10.1039/c5ra15469c
|View full text |Cite
|
Sign up to set email alerts
|

Triple helical collagen-like peptide interactions with selected polyphenolic compounds

Abstract: Because collagen is the most abundant component of connective tissue, it is an excellent biomaterial in numerous medical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…And the Rpn value decreased to 0.098 when the dosage of proyanidin increased to 40%. It has been reported that the micro unfolding of the collagen triple helical structure rather than denaturing was observed under the effect of phenolic compound and the corresponding Rpn values decreased (27,(33)(34). Therefore, the decreasing of Rpn values here was probably attributed to the conformational change of collagen molecule, which agreed well with the investigation of AFM (globular aggregates shown in Figure 1e and f).…”
Section: Circular Dichroism (Cd) Studiessupporting
confidence: 88%
“…And the Rpn value decreased to 0.098 when the dosage of proyanidin increased to 40%. It has been reported that the micro unfolding of the collagen triple helical structure rather than denaturing was observed under the effect of phenolic compound and the corresponding Rpn values decreased (27,(33)(34). Therefore, the decreasing of Rpn values here was probably attributed to the conformational change of collagen molecule, which agreed well with the investigation of AFM (globular aggregates shown in Figure 1e and f).…”
Section: Circular Dichroism (Cd) Studiessupporting
confidence: 88%
“…Three models were created for study; a wild-type, which is an extension to the unit-cell of the 4Z1R crystal structure of a collagen-like peptide [ 38 ], a model with a lysine and arginine side chain substituted between two polypeptide chains at residue positions 17 and 49 respectively, and a glucosepane cross-link between two polypeptide chains of the same collagen molecule at positions 17 and 49. Only one collagen molecule from the eight available was modified (with the exception to the wild-type) in the final extended unit cell.…”
Section: Methodsmentioning
confidence: 99%
“…The interactions between constituents in functional foods can potentially influence their biological activity. Many studies have revealed the interactions between phenolic compounds and other bioactive compounds, including proteins and peptides. More importantly, the interaction between peptides and phenols can even improve the in vitro antioxidant capacity of DWMH . Apart from direct improvements in efficacy, the interactions between bioactive ingredients also enhance performance by optimizing their pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 99%